Experimental and theoretical investigations of glass-fibre reinforced composite subjected to uniaxial compression for a wide spectrum of strain rates (Archives of Mechanics - Test, 2006)
Results of static and dynamic compression tests for two types of glass fibre-reinforced polypropylene composites are presented. Stress-strain curves showing the influence of the strain rate on the composite mechanical properties have been obtained. A three-dimensional description of the material behavior during the deformation has been developed. The material constitutive parameters have been calculated. Specification of the parameters and description of the methods used for their identification have been worked out. The results are discussed in terms of the deformation processes and the material non-homogeneity.